PERAN KOMANDO OPERASI KHUSUS (KOOPSUS) TNI DALAM PEMBERANTASAN TINDAK PIDANA TERORISME - Ramadhan Aji Pamungkas; Hari Soeskandi (Gapenas Publisher, 2022)
There is no further regulation regarding the role played by Special Operations Command Of The Indonesian National Armed Forces in eradicating the Crime of Terrorism through Military Operations Other Than War as stated in the TNI Law Article 7 paragraph (2) letter (b) number 3 through the main tasks of the TNI through OMSP to overcome acts of terrorism, so that there is a legal ambiguity in it and raises a question about the role and authority of the Special Operations Command Of The Indonesian National Armed Forces in the Eradication of Criminal Acts of Terrorism, as well as to what extent the Special Operations Command Of The Indonesian National Armed Forces can be deployed in the Eradication of Criminal Acts of Terrorism. Using normative legal research with statute approach and conceptual approach. This study explains that the role and authority of the Special Operations Command Of The Indonesian National Armed Forces in the Eradication of Criminal Acts of Terrorism is as an auxiliary task. In the context of terrorism crimes, the Special Operations Command Of The Indonesian National Armed Forces is involved in the Eradication of Criminal Acts of Terrorism which is carried out as an auxiliary task and there are limitations in the involvement of the Special Operations Command Of The Indonesian National Armed Forces in the Eradication of Terrorism Crimes such as the situation and conditions, place, time, and the level of threat that the Special Operations Command Of The Indonesian National Armed Forces can take action to the field in combating terrorism operations